Proposição de projeto de um sistema de distribuição de água para dois bairros no município de Tucuruí-PA - PRAIA, Gabriela Teles (2021)
The objective of this work was to present a proposal of a water distribution system for the Serra Azul and Popular neighborhoods, in Tucuruí-PA. To do this, the physical data of these districts were obteined, such as topography and number of people per residence, which are necessary to elaborate the map of the road network and the three different conceptions, with the aid of AutoCad version 2019. Subsequently, the hydraulic behavior of the three distribution lines was analyzed, in the EPANET 2.0 software: design alternative 1, design alternative 2 and design alternative 3, considering the recommendations of NBR 12218/94. With the results, it was observed that of the three alternatives proposed, alternative 1 can be characterized as the best conception, since it presents greater reliability, since its pressures will be regularized by a high reservoir, whose probability of being inoperative is low and the maintenance is considerably simple, and by a set of PRV's. At first, it can generate a high implantation cost compared to alternatives 2 and 3, since the volume of the high reservoir that will supply the Popular neighborhood and the Serra Azul neighborhood will be greater. However, it is possible that the expenses with the construction of the reservoir will, over time, be amortized with the economy in the expenditures with electric energy that would be consumed to operate the systems of alternatives 2 and 3.